Comparative Outcomes of Posterior Spinal Fusion and Vertebral Body Tethering in Moderate-to-Severe Adolescent Idiopathic Scoliosis: A Systematic Review and Meta- Analysis - Jati, Oktavio Jalu Kuncoro; Napitupulu, Regina Florean; Ramadhan, Muhammad Genta; Zidane, Ahmad; Putra, Gede Brahmantya Prinata; Oka, Gde Bagus Susila Pradnyana Nurcahyo; Cruz, Elmer Sebastian (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2026)
Adolescent scoliosis requiring surgical correction is commonly treated with posterior spinal fusion, a procedure that provides reliable deformity correction but reduces spinal mobility. Vertebral body tethering has emerged as a motion-preserving alternative, yet its comparative effectiveness and long-term safety remain uncertain. This systematic review and meta-analysis aimed to evaluate the radiographic, perioperative, functional, and safety outcomes of fusion and tethering techniques in adolescents with scoliosis. A comprehensive search of major databases identified eleven comparative studies that met the inclusion criteria. Pooled analyses demonstrated that fusion achieved superior radiographic correction, including lower final curve magnitudes and greater percentage and absolute curve correction. Tethering showed perioperative advantages, such as shorter operative time, reduced blood loss, and shorter hospital stay, while patient-reported outcomes were generally similar between techniques. However, tethering was associated with significantly higher complication and revision rates, primarily related to mechanical failure of the tether construct. Overall, these findings suggest that tethering may offer short-term recovery benefits for selected skeletally immature patients, whereas fusion remains the more predictable and durable option for achieving optimal curve correction. Further long-term comparative studies are needed to clarify the appropriate clinical role of tethering in the surgical management of adolescent scoliosis.